The effect of â€œTB Matahoâ€ health cadres in improving self-care capacity of patients with pulmonary tuberculosis - Muhtar, Muhtar; Aniharyati, Aniharyati (Universitas Muhammadiyah Semarang, 2021)
TB is still a public health problem throughout the world where Indonesia is a country that has the third largest number of TB sufferers after India and China. Self-care by patients and families during the treatment process was the key to healing pulmonary TB. Using a quasi-experimental method, this study aims to improve the ability of self-care for pulmonary TB patients through intervention by â€œTB Matahoâ€ health cadres. Most of the self-care capacity of pulmonary TB patients with pre-test results were sufficient, in the treatment group (75.2%) and the control group (62.5%). The post-test results for the treatment group were in the good category (53.1%) and the control group was in the sufficient category (59.4%). The results of the Paired Samples Test analysis in the treatment group obtained a value of p = 0.001 (p <0.05), which means that there was a significant difference in self-care capacity of pulmonary TB patients before and after treatment, as well as the results of the Independent Samples Test analysis, the p value was obtained. 0.030 (p <0.05) which means that there was a significant difference in the post-test results in the treatment group and the control group. Researchers recommend that pulmonary TB survivors who have a basic education of secondary and above can be trained to become health cadres and share their successful experiences with pulmonary TB patients who are still undergoing treatment programs.